Recent Existence Results for Second-Order Singular Periodic Differential Equations. (8th June 2009) - Chu, Jifeng; Nieto, Juan J.
Abstract : We present some recent existence results for second-order singular periodic differential equations. A nonlinear alternative principle of Leray-Schauder type, a well-known fixed point theorem in cones, and Schauder's fixed point theorem are used in the proof. The results shed some light on the differences between a strong singularity and a weak singularity.